Importance of Kaizen Principles for Business Success - Ghaleb, Belal Dahiam Saif (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
Kaizen, a Japanese philosophy meaning "continuous improvement," has become a foundational management approach worldwide, underpinning sustainable business success. This article explores the significance of Kaizen principles in diverse organizational settings by analyzing its historical origins, core tenets, and measurable impacts on productivity, waste reduction, employee engagement, and customer satisfaction. Utilizing a comprehensive literature review methodology, this study synthesizes empirical data and case studies across manufacturing, healthcare, and service industries. Findings confirm that organizations embedding Kaizen into their culture achieve superior operational efficiency, innovation capacity, and competitive advantage. The discussion addresses challenges, cultural considerations, and implementation strategies, concluding with evidence-based recommendations to maximize Kaizen's organizational value. This detailed study contributes a vital resource for future research and practical application of continuous improvement methodologies.